Origins, Functioning, and Objectives of the Región Centro, Argentina: 20 Years Since the Córdoba Protocol. (Desarrollo, Estado y Espacio, 2025)
The Region Centro is a subnational integration body composed of the Argentinian provinces of Córdoba, Santa Fe, and Entre Ríos. It was established in 1998, but its institutional activity began with the Córdoba Protocol in 2004. On the occasion of this 20th anniversary, this work aims to analyze the origins, institutional functioning, and objectives that have shaped the regional agenda. This qualitative study seeks to interpret the events that shaped the regionalization process and its evolution in the fields of federalism and intergovernmental relations, the promotion of productive development and infrastructure, and international projection. Regarding the theoretical framework, the study is grounded in the literature on the political economy of regionalism, which seeks to understand the relationship between territory and society in the global economy. The work concludes with reflections on the evolution of the Región over its 20 years of operation and raises new questions about its institutional framework and functioning in a different historical context.
Keywords: Regionalism; subnational integration; Región Centro; territorial development